(untitled) (Global Journal of Human-Social Science, 2019)
The present work aims to present the activity of writing of the self as an existential practice and that when developing as a problematization of everyday practices produces a new use of the technique in philosophy teaching Part of this text is a synthesis of the reflections of our doctoral thes is and on the other the exercise of potentializing by means of writing of the self the practice the teaching of philosophy in the technological education of the Federal Institutes Having as theoretical reference the philosophy of Michel Foucault this work is developed in two moments first we describe about the teaching of philosophy in technical high school and then we present Foucault s interpretation of philosophy as problematization of practices through the experience of writing of the self Our objective initially is to present a diagnosis of the technical use of philosophy education in technological education because philosophy becomes a technical procedure when seeking self-recognition in the production of truth and transmission of abstract content a practice that leads to impoverishment of the experience of self